The effects of Corporate Governance, Audit Quality, and Conservatism on Loan Collateral Requirements - Sansaloni Butar Butar (Jurnal Akuntansi dan Keuangan, 2020)
In competitive credit markets, borrowers and lenders have equal information on default risks. Under these circumstances, loan collateral are less important in credit decision-making. But in emerging credit market,  like Indonesia, borrowers and lenders do not possess equal information on firms’ future prospect, making use of collateral in mitigating default risk have become common practice. Despite strong theoretical support for the use of collateral to protect lenders from default risk, excessive protection may have a negative effect on the debt markets. However,  some Indonesian firms are not required to provide collateral for bank debts. This study examines the effect of Board of Commissioners independence, governance committees, audit quality, and conservatism on the likelihood of using loan collateral. Using slovin formula, as much as 785 firm listed in Indonesia Stock Exchange were collected during sample period of 2012-2015.  Logistic regression analysis suggest that firms with higher Board of Commissioners independence, having separate governance committee, hire Big 4 auditors, apply conservative accounting policies are less likely to provide loan collateral.